Actividad física relacionada con sobrepeso en estudiantes de la carrera de Geología Ambiental y Ordenamiento Terriotorial de la Universidad Nacional de Loja - Alván Rueda, Vanessa Cecibel (2015)
The research entitled: PHYSICAL ACTIVITY RELATED TO OVERWEIGHT IN STUDENTS RACE AND TERRITORIAL ENVIRONMENTAL GEOLOGY OF THE NATIONAL UNIVERSITY OF LOJA, evaluated the relationship between physical activity and overweight, whereas a lack of physical activity is one of the Main causes of the increase in overweight and obesity. Indeed, modern life has made changes in our work systems, forms of transportation, recreation and household activities, which together have resulted in a significant saving of energy before we spent in physical activity. It is a study of descriptive and transversal. The sample consists of 140 students where 19.61% are women and 63.57% are male. The tabulation and analysis were performed using the tables, which indicates that both overweight men and women in similar percentages, respectively, and the same percentage of obesity was found not much difference between the sexes. Regarding the level of physical activity, over 50% of women and men are at a low level, the average minutes spent sitting students was 505 minutes (8.4 hours per day). A moderate level in 31.37% of women and 39.32% of men. Getting itself to conclude that there is a considerable percentage of the population with low levels of physical activity, which is related to the rates of overweight and obesity in both sexes. Keywords: physical activity, overweight, students.